Wallet Attached Storage—Expanding the Usability of W3C Verifiable Credentials (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
The Digital Credentials Consortium (DCC) is a global network of postsecondary education institutions working together to develop open standards-based infrastructure and tools for issuing, sharing and verifying W3C Verifiable Credentials (VCs) and aligned standards like Open Badges 3.0 (OBv3). Through pilots and real-world implementations with educational institutions and employers, the DCC has identified key usability challenges and opportunities for improvement in Learning and Employment Record (LER) solutions. This presentation introduced Wallet Attached Storage (WAS), an innovative specification designed to address these challenges and significantly enhance the practical usability of VCs and OBv3s.  This poster presentation described how current digital credential systems often require recipients to manage and share credentials through siloed wallet applications, limiting interoperability and creating friction in verification processes. WAS addresses these limitations by leveraging the cryptographic key management functionality inherent to VCs and OBv3s, enabling wallet holders to securely connect their credentials to cloud storage platforms of their choice. This approach transforms how credentials can be shared and verified in real-world contexts. The specification allows credential holders to store their VCs alongside supporting evidence of skills and achievements in familiar cloud storage environments. Users can then share these materials through public or access-controlled cloud storage, providing verifiers with richer context while maintaining cryptographic security and user control. By bridging the gap between credential wallets and existing storage infrastructure, WAS makes digital credentials more accessible and practical for everyday use in educational and employment settings.  Keywords: W3C (worldwide web consortium), verifiable credentials, open badges, digital credentials, wallet attached storage, open standards